INDUSTRI PENDIDIKAN DAN HILANGNYA KEPEKAAN SOSIAL - Boy ZTF, Pradana (Jurnal Bestari, 2008)
One of the most striking facts of the decade is the enormous tendency of capitalization of education. Although education is basic need for human beings, having adequate education is difficult to achieved by all human beings, especially by the poor. Education costs people high price and this prevents poor people from affording education. this article explores this tendency and offers a solution that Islamic organizations, especially Muhammadiyah, can take to solve this problem. The article also suggests that in its early periods, Muhammadiyah has practiced an education for all, namely a mass education that is designed for people with economic strain. However, Muhammadiyah's recent practice of education has lost this values and it is even trapped in the practices of education industrialization. Consequently, education is transforming into commodities that can be achieved through sale and buying mechanism. Islamic organizations, including Muhammadiyah, have to take part in solving this problem.